2016
DOI: 10.1111/cbdd.12903
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the structure of the trace amine‐associated receptor 2: Homology modelling studies exploring the binding mode of 3‐iodothyronamine

Abstract: Recent studies have further investigated the trace amine-associated receptor type 2 (TAAR2) pharmacology, revealing its role not only at the olfactory sensory neurons but also at the immune system, being expressed in human leucocytes. In particular, the ability of this receptor to bind the unselective TAAR ligand 3-iodo-thyronamine (T AM) was elucidated, making in the meanwhile the discovery of selective compounds a urgent need to derive much more suitable tools for studying TAARs. In this context, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
7
1
2
Order By: Relevance
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011).…”
Section: E 3-iodothyronaminementioning
confidence: 69%
See 1 more Smart Citation
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011).…”
Section: E 3-iodothyronaminementioning
confidence: 69%
“…Recent attempts have been made to apply structurebased in silico computational protocols to the development of TAAR2 homology models for the prediction of TAAR2 ligands (Cichero and Tonelli, 2017). With a consensus TAAR defining motif now identified, further development of such models is expected to provide new leads and the identification of TAAR2-selective ligands, which will be a major boost to elucidating its physiologic roles.…”
Section: Trace Amines and Their Receptorsmentioning
confidence: 99%
“…78 and docking data calculated by Cichero et al . 79 . For further validation of the binding mode, we also carried out a molecular dynamics (MD) simulation as described below.
Figure 4Detailed interactions between Amphetamine and TAAR1.
…”
Section: Resultsmentioning
confidence: 99%
“…Следствием этого процесса является рассеяние избытка энергии в виде тепла. Однако применение галотана значительно угнетает норэпинефрин-индуцированный термогенез, причем этот эффект является обратимым, дозозависимым и не представляет собой вторичное следствие гипотермии и/или гипоксии [31,32]. Со своей стороны, тиронамин модулирует активность субмитохондриальных частиц и растворимой субъединицы F1 ATФазы, снижая потребление кислорода и усиливая продукцию перекиси водорода митохондриями.…”
Section: рисунок 1 динамика ректальной температуры тела исследуемых unclassified